The role of defenders' and victims' popularity in the effectiveness of defending in bullying interactions: A longitudinal social network study - Richters, Stefanie; van Zalk, Maarten H. W.; Veenstra, René; Laninga‐Wijnen, Lydia (John Wiley & Sons, 2026)
Peer defending is widely promoted as a strategy to reduce bullying, but few studies haveinvestigated whether having more defenders decreases victimization over time from thevictim's perspective. This social network study examined the longitudinal associationbetween nominating more defenders and subsequent victimization among (early) ado-lescents and tested whether this relation is moderated by the popularity status of the de-fender and the victim. The sample included 1450 participants from 93 secondary schoolclasses (grades 4–9) in Finland (52.51% female; Mage = 12.38 years, SD age = 1.56). Resultsfrom longitudinal social network analyses showed that contrary to expectations, havingmore defenders did not reduce victimization over time. Moreover, the popularity of thedefender or the victim did not moderate this effect. Results did not differ by grade. Thesefindings suggest that defending alone may not protect students from ongoing victimiza-tion and highlight the need for broader, multi-level intervention strategies.